2019
DOI: 10.1186/s13287-019-1472-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to blue light stimulates the proangiogenic capability of exosomes derived from human umbilical cord mesenchymal stem cells

Abstract: BackgroundThe therapeutic potential of mesenchymal stem cells (MSCs) may be attributed partly to the secreted paracrine factors, which comprise exosomes. Exosomes are small, saucer-shaped vesicles containing miRNAs, mRNAs, and proteins. Exosomes derived from human umbilical cord mesenchymal stem cells (hUC-MSCs) have been reported to promote angiogenesis. However, the efficacy of exosome-based therapies is still limited both in vitro and in vivo. The present study aimed to develop a new optical manipulation ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 33 publications
(38 reference statements)
2
56
0
Order By: Relevance
“…In addition to such bioactive substances, environmental factors impact the proangiogenic properties of MSC-exosomes. In fact, exposure of MSCs to blue light resulted in the increased content of miRNA-135b-5p and miRNA-499a-3p as exosomal cargo, which promoted angiogenesis in vitro by repressing myocyte enhancer factor 2C (MEF2C) [66]. Consistent with this finding, hypoxia enhanced the cargo content of miRNA-126 in MSC-exosomes.…”
Section: Angiogenesissupporting
confidence: 58%
“…In addition to such bioactive substances, environmental factors impact the proangiogenic properties of MSC-exosomes. In fact, exposure of MSCs to blue light resulted in the increased content of miRNA-135b-5p and miRNA-499a-3p as exosomal cargo, which promoted angiogenesis in vitro by repressing myocyte enhancer factor 2C (MEF2C) [66]. Consistent with this finding, hypoxia enhanced the cargo content of miRNA-126 in MSC-exosomes.…”
Section: Angiogenesissupporting
confidence: 58%
“…Under blue light exposure, HuC-MSC-Ex can promote angiogenesis in vivo and enhance its ability to promote angiogenesis. It was confirmed that the exosomes treated by blue light stimulated the activation of endothelial cells by upregulating the two miRNAs of mir-135b-5p and mir-499a-3p [79].…”
Section: The Therapeutic Effects Of Exosomes From Huc-mscsmentioning
confidence: 75%
“…Yang et al showed that blue light exposure could elevated levels of miR-135b-5p and miR-499a-3p to increased proangiogenic capacity in MSC-exos. 63 Therapy based on photon energy has been broadly recommended as a method to accelerate diabetic wound healing. A future strategy for wound management might involve a noninvasive, economical, and multipurpose lightdependent cellular treatment.…”
Section: Discussionmentioning
confidence: 99%